2016
DOI: 10.1088/0029-5515/57/1/016003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrode biasing on m/n  =  2/1 tearing modes in J-TEXT experiments

Abstract: The effects of electrode biasing (EB) on the m/n = 2/1 tearing mode have been experimentally studied in J-TEXT tokamak discharges, where m and n are the poloidal and toroidal mode numbers. It is found that for a negative bias voltage, the mode amplitude is reduced, and the mode frequency is increased accompanied by the increased toroidal plasma rotation speed in the counter-I p direction. For a positive bias voltage, the mode frequency is decreased together with the change of the rotation velocity towards the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…If the EB current is sufficiently negative, the local plasma as well as the 3/1 mode is forced to rotate, which will in turn pull the locked 2/1 mode toward mode unlocking via mode coupling. This mechanism is distinctive with those mentioned before, and could be response for the fast response of mode frequency to EB current shown in figure 2 and the experimental results in the previous work [39,40] . In general, the interaction between the locked island and RMP can be seen as braking torque in the unlocking process, while the interaction between the locked island and EB as driving torque.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…If the EB current is sufficiently negative, the local plasma as well as the 3/1 mode is forced to rotate, which will in turn pull the locked 2/1 mode toward mode unlocking via mode coupling. This mechanism is distinctive with those mentioned before, and could be response for the fast response of mode frequency to EB current shown in figure 2 and the experimental results in the previous work [39,40] . In general, the interaction between the locked island and RMP can be seen as braking torque in the unlocking process, while the interaction between the locked island and EB as driving torque.…”
Section: Discussionsupporting
confidence: 77%
“…It increases the rotation derivation ∆Ω 𝜃 , which strengthens the viscous torque and pulls the locked magnetic island to the unlocking direction. The momentum transport can also increase the flow shear at the rational surface [34,39] , which is a candidate to weaken the intensity of Ψ, and induces the unlocking. The other way is that the improved confinement under biasing could increase the electron temperature to heighten the natural frequency according to the equation( 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the experimental and modeling results have focused on stable and healthy plasma, which is obviously different for the actual situation in ITER. For the inevitable disruption in ITER, uncontrolled modes, which can be controlled for instance by a combination of applied resonant magnetic perturbation (RMP) [19][20][21], electron cyclotron current drive [22] and electrode biasing [23], are likely to appear before the application of DMS [24]. In addition, statistical studies of disruptions on JET have found that they nearly all exhibit signs of mode locking before the disruption takes place [25].…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…Electrode biasing has also been used to achieve the high confinement H-mode regime as was done in the CCT [20] and HBT-EP [21] tokamaks as well as broaden heat loads at the plasma edge as done in the HYBTOK-II [22] and DIII-D [23] tokamaks. Static electrode biasing has been shown to suppress mode amplitudes in several tokamaks [24][25][26][27][28]. The only previous investigation of closed-loop active control of instabilities with electrode biasing was conducted on the T-10 tokamak [29,30] where a single biased limiter was phase-locked to an m = 2 internal tearing mode and was able to suppress it.…”
mentioning
confidence: 99%